The short-term efficacy of vena cava filters for the prevention of pulmonary embolism in patients with venous thromboembolism receiving anticoagulation: Meta-analysis of randomized controlled trials. (October 2017) - Jiang, Jun; Jiao, Yuanyong; Zhang, Xiwei
Objectives: To perform a meta-analysis of randomized controlled trials assessing the effectiveness of inferior vena cava filters in patients with deep vein thrombosis for preventing pulmonary embolism. Method: Relevant randomized controlled trials of inferior vena cava filters for the prevention of pulmonary embolism were identified by searching electronic databases updated in February 2016. Relative risks of recurrent pulmonary embolism, recurrent deep vein thrombosis, and mortality at three months were analyzed. Results: Three published randomized controlled trials were included involving a total of 863 deep vein thrombosis patients. No significant differences were detected with inferior vena cava filters placement with regard to the incidence of recurrent pulmonary embolism or fatal pulmonary embolism. There were also no significant differences in the incidence of recurrent deep vein thrombosis or mortality with inferior vena cava filters placement at three months. Conclusions: Inferior vena cava filter in addition to anticoagulation was not associated with a reduction in the incidence of recurrent pulmonary embolism as compared with anticoagulation alone in patients with deep vein thrombosis in the short term.